Intrahousehold Resource Allocation and Individual Poverty: Assessing Collective Model Predictions against Direct Evidence on Sharing - Olivier Bargain; Guy Lacroix; Luca Tiberti (Institute of Labor Economics (IZA), 2021)
Welfare analyses conducted by policy practitioners around the world usually rely on equivalized or per-capita expenditures and ignore the extent of within-household inequality. Recent advances in the estimation of collective models suggest ways to retrieve the complete sharing process within families using homogeneity assumptions (typically preferences stability upon exclusive goods across individuals or household types) and the observation of exclusive goods. So far, the prediction of these models has not been validated, essentially because intrahousehold allocation is seldom observed. We provide such a validation by leveraging a unique dataset from Bangladesh, which contains information on the fully individualized expenditures of each family member. We also test the core assumption (efficiency) and homogeneity assumptions used for identification. It turns out that the collective model predicts individual resources reasonably well when using clothing, i.e., one of the rare goods commonly assignable to male, female and children in standard expenditure surveys. It also allows identifying poor individuals in non-poor households while the traditional approach understates poverty among the poorest individuals.
Keywords: D11; D12; D36; I31; J12; 330; collective model; Engel Curves; Rothbarth Method; sharing rule